2021
DOI: 10.1038/s41598-021-99809-5
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal cohort study on benefit finding evolution in Chinese women breast cancer survivals

Abstract: Even though the prevalence of benefit finding (BF) has been empirically shown to exist among breast cancer (BC) survivals, how does benefit finding evolve over time remains inadequately investigated. The objective of this cohort study is to examine how BF evolves over time among Chinese breast cancer survivals and determine the demographic, medical and psychosocial factors that can sustain BF increase over time. Participants were 486 women with different stages of breast cancer (stages I, II and III) followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
(31 reference statements)
2
7
0
Order By: Relevance
“…The overall PTG trend of both the "Steady increase" and "Fluctuated rise" groups was increasing in the following 2 years despite the fluctuation in the second year (March 2021). Similar to previous studies on PTG and the development process of individuals diagnosed with a disease such as COVID-19 or cancer (19,27), this result proves that the relationship between traumatic events and PTG is not a single linear relationship. PTG changes over time with significant inter-individual heterogeneity, and this must be considered to better understand the response to prolonged adverse situations and is also crucial for hospital managers to improve the psychological health of HCWs.…”
Section: Discussionsupporting
confidence: 89%
“…The overall PTG trend of both the "Steady increase" and "Fluctuated rise" groups was increasing in the following 2 years despite the fluctuation in the second year (March 2021). Similar to previous studies on PTG and the development process of individuals diagnosed with a disease such as COVID-19 or cancer (19,27), this result proves that the relationship between traumatic events and PTG is not a single linear relationship. PTG changes over time with significant inter-individual heterogeneity, and this must be considered to better understand the response to prolonged adverse situations and is also crucial for hospital managers to improve the psychological health of HCWs.…”
Section: Discussionsupporting
confidence: 89%
“…Some studies applied the Functional Assessment of Chronic Illness Therapy -Spiritual Well-being scale (FACIT-SP), a scale that includes meaning but assesses predominantly spirituality. These studies had to be excluded seeing as they considered meaning to either be a synonym or a component of spirituality (e.g., Park and Cho, 2017;Bi et al, 2021). The included studies applied different instruments to assess MiL, which can be a threat to the validity of the results obtained by the meta-analysis.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Consequently, this study was limited in exploring whether the trajectory of social support, spirituality, and benefit finding varied across patients at different times. A longitudinal cohort study on benefit-finding evolution in 486 women with different stages of breast cancer showed that social support was not related to benefit-finding trends; in comparison, spirituality level at diagnosis was a more reliable predictor of benefit-finding evolution over time 50 . We recommend using longitudinal designs to examine how changes in social support and spirituality are linked to the evolution of benefit finding in patients with advanced cancer in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal cohort study on benefit-finding evolution in 486 women with different stages of breast cancer showed that social support was not related to benefit-finding trends; in comparison, spirituality level at diagnosis was a more reliable predictor of benefit-finding evolution over time. 50 We recommend using longitudinal designs to examine how changes in social support and spirituality are linked to the evolution of benefit finding in patients with advanced cancer in future studies. Moreover, whether alternative models exist remains to be investigated in depth.…”
Section: Limitations and Recommendations For Future Studiesmentioning
confidence: 99%